The Chest and Radiological Features of Covid-19 - Kenis Shedrack Felangu; Chidozie Valentine Adiukwu; Abdulkarim Ibrahim Dahiru; Khadija Abimbola Abdulraheem; Ugochukwu Anthony Eze (Clinical Manifestations of Covid-19: A Multi-Disciplinary Approach, 2024)
Originally reported as a respiratory disease, but with more understanding of the condition, systemic components have been fairly described. Features could be mild, moderate and severe. SARS-CoV-2 has been reported to bind ACE 2 receptors which ultimately results and in an eventual ARDS due to increased pulmonary surface tension. Radiologic features are essential of the chest and serve as surrogate diagnostic markers and for prognostication. Computed tomography (CT) is the radiological test. Conventional X-ray on the other hand is less sensitive and specific compared to the former but usually, it is the first-line imaging modality used for suspected Covid-19 cases. Findings may be normal in early or mild disease severe cases show abnormal signs which may be categorized as probable/classic, intermediate for Covid-19, non-Covid-19, or normal (note that normal does not exclude Covid-19). These abnormalities are usually bilateral, involving the lower lobes with predominant air space opacification, interstitial infiltrates, or patchy consolidation.